2016
DOI: 10.3390/app6080222
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and Biomedical Applications of Gold Nanoparticles Using Eclipta prostrata Leaf Extract

Abstract: This study reports the biological synthesis of gold nanoparticles (AuNPs) by the reduction of HAuCl 4 by using of Eclipta prostrata leaf extract as the reducing and stabilizing agent. AuNPs were characterized using Ultraviolet-visible (UV-vis) spectroscopy, X-ray diffraction (XRD), Fourier Transform-Infrared (FTIR) spectroscopy, Scanning Electron Microscopy (SEM), High Resolution-Transmission Electron Microscopy (HRTEM), and Energy Dispersive X-ray analysis (EDAX). The UV-visible spectrum of the synthesized Au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 45 publications
4
25
0
1
Order By: Relevance
“…Researchers has reported that synthesized AgNPs may have significant impact on malaria causing vectors and our results are in line with the previous results [17,18,26] similarly, Velayutham et al, [27] reported silver nanoparticles synthesized using bark aqueous extract of F. racemosa represented maximum larvicidal activity against the larvae of disease spreading vectors which is agrement with our study.…”
Section: Larvicidal Activity Of Nanoparticle Extract Of Terrestrial Psupporting
confidence: 93%
See 1 more Smart Citation
“…Researchers has reported that synthesized AgNPs may have significant impact on malaria causing vectors and our results are in line with the previous results [17,18,26] similarly, Velayutham et al, [27] reported silver nanoparticles synthesized using bark aqueous extract of F. racemosa represented maximum larvicidal activity against the larvae of disease spreading vectors which is agrement with our study.…”
Section: Larvicidal Activity Of Nanoparticle Extract Of Terrestrial Psupporting
confidence: 93%
“…AgNPs were synthesized from the whole plant material (Phyllanthus amarus, Annona squamosa, Coccinia grandis and Eclipta prostrata) by the method explained by Rajakumar and Rahuman, [17]. Fig.…”
Section: Synthesis Of Silver Nano Particlementioning
confidence: 99%
“…Numerous methods have been reported for the synthesis of noble metal-based nanoparticles, such as chemical reduction, hydrothermal, solvothermal, and thermal annealing methods, with controlled size and shape [13][14][15][16][17]. Among the noble metal-based nanomaterials, gold nanoparticles have been widely exploited for biomedical applications due to their peculiar properties such as chemical, optical, electrical, and catalytic biocompatibility and its ability to conjugate with biomolecules [18]. Silver nanoparticles have also been extensively explored for practical applications due to their highly selective and sensitive performance towards the detection of biomolecules [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…; Rajakumar et al . ; Rajakumar & Rahuman ; Rajasekar et al . 2016) and assessment of their curative activity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition it has been shown to have anti-HIV, antivenom, antidiabatic and antihelmintic attributes (Pithayanukul et al 2004;Tewtrakul et al 2007;Jahan et al 2014;Nathiya & Gayathri 2016;Kousalya et al 2017), and can protect against nurotoxicity (Jaisin et al 2016), infertility (Hung et al 2016), hepatotoxicity (Himaja and Neelufar Shama, 2015), and gastrointestinal disorders (Neamsuvan & Ruangrit 2017). These curative properties, especially against cancer and HIV, have led to extensive studies on nanoparticles synthesized biomimetically using aqueous extracts of E. prostrata (Chung et al , 2017Rajakumar et al 2012Rajakumar et al , 2015Rajakumar et al , 2016Rajakumar & Rahuman 2011;Rajasekar et al 2016) and assessment of their curative activity. Another manner in which E. prostrata has also been utilized is as a biosorbant (Chandra & Yadav 2017).…”
Section: Introductionmentioning
confidence: 99%